2014
DOI: 10.1109/tbc.2014.2359255
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Quality Assessment of Longer Duration Video Sequences Delivered Over HTTP Adaptive Streaming to Tablet Devices

Abstract: Abstract-HTTP Adaptive Streaming facilitates video streaming to mobile devices connected through heterogeneous networks without the need for a dedicated streaming infrastructure. By splitting different encoded versions of the same video into small segments, clients can continuously decide which segments to download based on available network resources and device characteristics. These encoded versions can, for example, differ in terms of bitrate and spatial or temporal resolution. However, as a result of dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…In addition, the impact of these factors in up-switching (increasing the quality) and down-switching (decreasing the quality) should be considered. The results presented in [5], [8], [9] showed that inserting intermediate levels between quality drops was favorable for the perceived quality, compared to switching directly to the target quality level. However, the results presented in [10] showed that, although down-switching is generally considered annoying, abrupt up-switching might even increase the QoE as users might be happy to notice the visual improvement.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, the impact of these factors in up-switching (increasing the quality) and down-switching (decreasing the quality) should be considered. The results presented in [5], [8], [9] showed that inserting intermediate levels between quality drops was favorable for the perceived quality, compared to switching directly to the target quality level. However, the results presented in [10] showed that, although down-switching is generally considered annoying, abrupt up-switching might even increase the QoE as users might be happy to notice the visual improvement.…”
Section: Related Workmentioning
confidence: 99%
“…Various observations were made including the preference of constant bitrate over frequently changing bitrate and a slow drop to the lower quality over oscillating bitrates. Staelens et al [37] performed a subjective study for long duration videos on tablet devices for investigating the impact of quality switches due to adaptive streaming. They observed that users mainly perceive the change of quality from the highest to the lowest levels and high to medium quality changes remain largely unnoticeable.…”
Section: Related Workmentioning
confidence: 99%
“…Another possible solution is presented by Staelens et al in [16], where the authors implemented a subjective quality assessment methodology into the application used for presenting video content on mobile devices. The authors were the owners of the mobile devices, and the prepared test sequences were stored locally on the devices.…”
Section: Introductionmentioning
confidence: 99%
“…During the streaming sessions, the button was pressed by the test subjects when they wanted to indicate noticing the frame freeze video artifact. Note that the study also assumed streaming of the content to the subjects' devices for rating and, similar to [16], the used methodology revealed the purpose of the test to the subjects.…”
Section: Introductionmentioning
confidence: 99%